Analysis Of The Impact Of Training And Employee Promotion On Employee Productivity With Motivation As A Mediator At Reliance Insurance Indonesia - Lumbanraja, Suharjo; Haryono, Budi; Njotowidjojo, Mina Sulastri (Pt. Anagata Sembagi Education, 2024)
The insurance industry is essential to a country's economy, offering risk management and financial protection for individuals and businesses. Maintaining service quality and competitiveness requires high-quality human resources (HR). Key challenges in HR include recruiting, training, and retaining skilled employees. Reliance Insurance Indonesia relies on knowledgeable, skilled, and motivated employees for the company's sustainability and growth. Factors such as training, professional education, awards, and promotions are essential to maintain employee relevance and motivation. Industry-related seminars, professional education, and certifications improve employees' abilities and confidence, as well as enhance customer trust and company reputation. Recognizing employees' contributions through international travel, bonuses, and salary increases further motivates them. Performance-based promotions encourage professional growth and advancement. This study examines the impact of training and promotion sessions on employee productivity, with motivation as a mediating factor, at Reliance Insurance Indonesia. Located in Reliance Insurance Indonesia with a total of 100 (one hundred) people, all members of the population are also sampled, so this study is a census study. The results of the analysis show that all indicators used in this study are valid and reliable. This study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This study provides evidence of a positive and significant influence